1979
DOI: 10.1136/gut.20.12.1066
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of an unfused pancreatic duct system.

Abstract: SUMMARY In man, the main pancreatic duct is normally derived from ventral and dorsal embryological buds of the pancreas. In a minority of people, failure of fusion of the two buds results in separate drainage of the dorsal and ventral pancreas, so that the accessory duct provides the main drainage for the gland. Patients with this anomaly demonstrated at endoscopic retrograde pancreatography (ERP) have been investigated to assess whether non-fusion of the main pancreatic duct predisposes to the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
2

Year Published

1981
1981
2005
2005

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(24 citation statements)
references
References 11 publications
(12 reference statements)
1
19
0
2
Order By: Relevance
“…In several reported series of cases examined by ERCP, pancreatic divisum has been recognized in 0.3% to 5.8% of the cases. 9,10 In this study, pancreatic divisum was found in 34 patients (5.1%). Duodenal diverticula are acquired lesions.…”
Section: Discussionmentioning
confidence: 54%
“…In several reported series of cases examined by ERCP, pancreatic divisum has been recognized in 0.3% to 5.8% of the cases. 9,10 In this study, pancreatic divisum was found in 34 patients (5.1%). Duodenal diverticula are acquired lesions.…”
Section: Discussionmentioning
confidence: 54%
“…It was first described by Hyrtl [1]in 1865 and is found in about 5–7% of the general population. The exact frequency in autopsy studies ranges from 4 to 11% [2, 3, 4]and in endoscopic pancreaticographic studies from 1.6 to 5.8% [5, 6, 7, 8, 9]. …”
Section: Discussionmentioning
confidence: 99%
“…Pancreas divisum is found in up to 10% of autopsy studies [35][36][37][38][39][40] and in 2-7% of the elective retrograde cholangiopancreatography series [41][42][43][44]. It is believed that when present in association with stenosis of the minor papilla, it causes resistance to pancreatic flow and may be responsible for patients presenting with acute recurrent pancreatitis and less certain for abdominal pain [41][42][43][44].…”
Section: Pancreas Divisummentioning
confidence: 99%
“…It is believed that when present in association with stenosis of the minor papilla, it causes resistance to pancreatic flow and may be responsible for patients presenting with acute recurrent pancreatitis and less certain for abdominal pain [41][42][43][44].…”
Section: Pancreas Divisummentioning
confidence: 99%
See 1 more Smart Citation